2021
DOI: 10.1159/000514071
|View full text |Cite
|
Sign up to set email alerts
|

Immune Dysfunction in Patients with Chronic Lymphocytic Leukemia and Challenges during COVID-19 Pandemic

Abstract: The novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) has been first described in December 2019 in Wuhan, China, and has led to a worldwide pandemic ever since. Initial clinical data imply that cancer patients are particularly at risk for a severe course of SARS-CoV-2. In patients with chronic lymphocytic leukemia (CLL), infections are a main contributor to morbidity and mortality driven by an impaired immune system. Treatment initiation is likely to induce immune modulation that further increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 82 publications
1
34
0
Order By: Relevance
“…Patients with chronic lymphocytic leukemia (CLL) have an increased risk of severe infections due to disease- and treatment-related immunodeficiency [ 1 , 2 ] that does not exclude novel precision therapeutics such as ibrutinib [ 3 , 4 ]. Two early international surveys reported that hospital-admitted Covid-19 patients with CLL had a high fatality rate [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic lymphocytic leukemia (CLL) have an increased risk of severe infections due to disease- and treatment-related immunodeficiency [ 1 , 2 ] that does not exclude novel precision therapeutics such as ibrutinib [ 3 , 4 ]. Two early international surveys reported that hospital-admitted Covid-19 patients with CLL had a high fatality rate [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is worth to be mentioned that in the current worldwide pandemic scenario, patients with CLL can be severely affected by SARS-CoV-2 infection [175]. Older patients seem to be at increased risk of infection, with a high incidence of mortality among hospitalized patients (reviewed in [176]). Interestingly, it has been postulated that BTK inhibitors such as ibrutinib or acalabrutinib could attenuate hyperinflammatory responses thus exerting protection against severe disease course, but to date data are still controversial and prospective clinical trials are ongoing [176]).…”
Section: Infectionsmentioning
confidence: 99%
“…This is due to an underlying immunodeficiency, inadequate immune response to infections and therapy-related immunosuppression 2 . The immune dysfunction in patients with CLL raises concern and represents a challenge during the COVID-19 pandemic 3 .…”
Section: Introductionmentioning
confidence: 99%